Association between maternal antibiotic exposure and emotional and behavioural problems in children at four years of age: A biomonitoring-based prospective study - Wanhong Xiong; Baolin Wang; Feifei Han; Juan Tong; Hui Gao; Peng Ding; Kaiyong Liu; Xiaoyan Wu; Kun Huang; Menglong Geng; Fangbiao Tao (Ecotoxicology and Environmental Safety)
Background: Maternal exposure to multiple antibiotics exposure during pregnancy has attracted extensive attention, but biomonitoring studies linking prenatal antibiotic exposure to emotional and behavioural problems in children are limited. Methods: A total of 2475 pregnant women from the Ma’anshan Birth Cohort were included, and the Strengths and Difficulties Questionnaire was completed when their children turned four years of age. The levels of 41 maternal urinary antibiotics and two metabolites were measured during the first, second and third trimesters. Generalized estimating equations and binary logistic regression models were applied to analyse the associations between maternal antibiotic exposure and emotional and behavioural problems in children and to determine the sensitive period, respectively. A quantile-based g-computation (QGC) approach was employed to examine the combined effects of multiple antibiotics on emotional and behavioural problems in children. Results: Overall, florfenicol and preferred-as-veterinary antibiotic (PVA) exposure during pregnancy increased the risk of emotional problems in children, and ofloxacin exposure increased the risk of hyperactivity-inattention. Maternal exposure to trimethoprime, ciprofloxacin, florfenicol, other antibiotics and PVA exposure during the first trimester was positively associated with emotional problems in children. Second-trimester trimethoprime concentrations and third-trimester ciprofloxacin concentrations were positively associated with hyperactivity-inattention. Third-trimester veterinary antibiotic (VA) exposure was negatively associated with hyperactivity-inattention, and second-trimester VA and PVA exposure was negatively associated with peer problems. The QGC model revealed that mixed antibiotic exposure in the first trimester exacerbated the risk of childhood emotional problems (the contribution of ciprofloxacin is prominent), and mixed antibiotic exposure in the second trimester increased the risk of hyperactivity-inattention (the contribution of trimethoprime is prominent). Conclusion: Maternal mixed antibiotic exposure during the first and second trimesters increases the risk of emotional problems and hyperactivity-inattention in children at four years of age.